Vertebroplasty and Kyphoplasty in the Treatment of Osteoporotic Vertebral Compression Fractures - Işıl Taş; Simin Hepgüler; Mehmet Zileli; Sedat Çağlı; Sertaç İşlekel (Galenos Yayinevi, 2004)
In our study which is carried out to detect the effect of kyphoplasty over acute vertebral fractures, 8 patients; presenting with 6 osteoporotic, 1 tumoral, 1 traumatic acute vertebra fractures underwent kyphoplasty procedure at a total of 12 levels. No postoperative complications were detected, and as achieved, in the 6 th and 12 th month follow up periods, no adjacent vertebral fracture was observed with X ray imaging. With this small series, kyphoplasty has been shown to have affirmative effects in the treatment of acute vertebral fractures with respect to the visual analogue scale, Qualeffo-41 questionnaire and morphometric vertebral height measurements.